Формування стратегії розвитку машинобудівного підприємства на основі збалансованої системи показників - Побережний, Роман Олегович (НТУ "ХПІ", 2015)
Дисертація на здобуття наукового ступеня кандидата економічних наук за спеціальністю 08.00.04 – економіка та управління підприємствами (за видами економічної діяльності). – Національний технічний університет "Харківський політехнічний інститут", Харків, 2015 р. Дисертацію присвячено вирішенню актуального науково-практичного завдання щодо розвитку теоретичних положень, методичного забезпечення і практичних рекомендацій з формування стратегій розвитку машинобудівних підприємств на основі збалансованої системи показників. У дисертації узагальнено економічну сутність та уточнено класифікацію розвитку підприємства; узагальнено підходи до формування збалансованої системи показників (ЗСП) та уточнено її; розроблено структурно-логічну послідовність етапів формування стратегій розвитку підприємства на основі ЗСП. Визначено тенденції розвитку промисловості, машинобудівних підприємств на макро-, мезо- та мікроекономічних рівнях. Розроблено методичний підхід до оцінювання рівня загального розвитку машинобудівних підприємства у внутрішньому середовищі з урахуванням ЗСП; запропоновано методичний підхід до визначення сприятливості зовнішнього середовища до розвитку машинобудівних підприємств; визначено кількісно-якісні межі рівнів загального розвитку та сприятливості зовнішнього середовища до розвитку для формування їх стратегій; обґрунтовано й розроблено модель формування стратегічного профілю машинобудівного підприємства, що включає корпоративні, конкурентні та функціональні стратегії розвитку.

Dissertation on the receipt of scientific degree of candidate of economic sciences after speciality 08.00.04 is an economy and management enterprises (after the types of economic activity). It is the National technical university the "Kharkiv polytechnic institute", Kharkiv, 2015. Dissertation is sanctified to the decision of actual research and practice task in relation to development of theoretical positions, methodical providing and practical recommendations from forming of strategies of development of machine-building enterprises on the basis of the balanced scorecard. In dissertation economic essence is generalized and classification of development of enterprise is specified; approaches are generalized to forming of the balanced scorecard (BSC) and it is specified constituents for forming of strategies of development; the structural and logical sequence of the stages of forming of strategies of development of enterprise is worked out on the basis of BSC. Progress of industry, machine-building enterprises trends are certain on macro-, meso- and microeconomic levels. The methodical going is worked out near the evaluation of level of general development of machine-building enterprises in an internal environment taking into account BSC; the methodical going is offered near determination of favorableness of machine-building enterprises to development in an environment; procedure of determination of in-quality limits of levels of general development and favorableness is offered to development of machine-building enterprises for forming of their strategies; reasonably and the model of forming of strategic profile of machine-building enterprise that includes corporate, competition and functional strategies of development is worked out.
Forming of strategy of development of machine-building enterprise is on the basis of the balanced scorecard
Keywords: управління підприємством; стратегії розвитку; збалансована система показників; рівень загального розвитку підприємств; стратегічний профіль; конкурентні стратегії; функціональні стратегії; дисертації; management of enterprise; development of enterprise; strategies of development; balanced scorecard; strategic profile; competition strategies; functional strategies; 658:005.21:621